(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The escalating demand for environmentally sustainable and cost-efficient methodologies for the removal of toxic metal ions from contaminated aquatic environments and the retrieval of valuable noble metal ions from various waste matrices, often relegated to the status of secondary sources, has precipitated a surge in the exploration of techniques rooted in polymer inclusion membranes (PIMs).